Long-Lasting Analgesia With Transdermal Fentanyl: A New Approach in Rat Neonatal Research - Dutriez-Casteloot, Isabelle; Emmanuelli, Virginie; Wiart, Jean-François; Tavernier, Annabelle; Besengez, Capucine; Storme, Laurent; Houfflin-Debarge, Véronique (Frontiers in Pharmacology, 2022)
Background With advances in neonatal care, management of chronic pain in newborns is a daily concern. In addition to ethical considerations, pain in early life would have long-term effects and consequences. However, its treatment remains inadequate. It was therefore important to develop an experimental model of long-lasting analgesia for neonatal research. Materials and methods Experiments were performed in 6 groups of rats with transdermal fentanyl 0, 3, 12, 50, 100 or 200µg/kg/h from second postnatal day (P2) until weaning. Assessment of analgesia was carried out at P21, with behavioural scores (ranging from 0 to 3) using a 4% formalin test. Plasma levels of fentanyl were determined by UPLC/QDT at P22. Growth rate was investigated. Results Fentanyl 100 and 200µg/kg/h reduced scores of formalin-evoked behavioural pain. They increased time spent in pain score 0(8min55sec and 6min34sec versus 23sec in controls) as in low pain score 1 and 2, and decreased time in the most severe pain score 3 (19min56sec and 17min39sec versus 44min15sec). Fentanylemia increased in a dose-dependent manner from 50µg/kg/h (2.36±0.64ng/mL) to 200µg/kg/h (8.66±1.80ng/mL). Concerning growth, no difference was observed except weaker growth from P17 to P22 with 200µg/kg/h. Clinically, we noticed no visible side effect from 3 to 100μg/kg/h. Concomitantly, 200μg/kg/h was responsible for ophthalmological side effects with appearance of corneal bilateral clouding in 90% pups. No difference was observed between male and female rats. Conclusion Altogether, results indicate that transdermal fentanyl 100µg/kg/h is an efficient therapeutic for long-lasting analgesia in lactating pups. This new model provides useful tool for protection and welfare, and future opportunity for studying long-term health consequences of sustainable neonatal analgesia.